Crop Failures and Export Tariffs - Pio Baake; Steffen Huck (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We analyze a stylized model of the world grain market characterized by a small oligopoly of traders with market power on both the supply and demand side. Crops are stochastic and exporting countries can impose export tariffs to protect domestic food prices. We show that export tariffs are strategic complements and that poor harvests can lead to a sharp increase in equilibrium tariffs. Due to the strategic interplay between the governments of exporting countries, traders can gain from a poor harvest in one of the countries. Furthermore, consumers in import countries can benefit from cooperation between grain exporting countries.
Keywords: D43; F12; L13; 330